Design, synthesis and computational evaluation of a novel intermediate salt of N-cyclohexyl-N-(cyclohexylcarbamoyl)-4-(trifluoromethyl) benzamide as potential potassium channel blocker in epileptic paroxysmal seizures. (October 2016) - Natchimuthu, V.; Bandaru, Srinivas; Nayarisseri, Anuraj; Ravi, S.
Graphical abstract: Highlights: A synthesis of novel intermediate salt of N -cyclohexyl- N -(cyclohexylcarbamoyl)-4-(trifluoromethyl) benzamide is reported. Structures established on the basis of IR, 1 H, 13 C NMR Spectra and X-ray diffraction analysis. Computational study on molecular docking and binding of the compound suggest, as the best potassium channel blocker in Blood Brain Barrier. Resulting analogues have good oxygen enriching capacity. Abstract: The narrow therapeutic range and limited pharmacokinetics of available Antiepileptic drugs (AEDs) have raised serious concerns in the proper management of epilepsy. To overcome this, the present study attempts to identify a candidate molecule targeting voltage gated potassium channels anticipated to have superior pharmacological than existing potassium channel blockers. The compound was synthesized by reacting (S)-(+)-2, 3-dihydro-1H-pyrrolo[2, 1-c][1, 4] benzodiazepine5, 11(10H, 11aH)-dione with 4-(Trifluoromethyl) benzoic acid (C8 H5 F3 O2 ) in DMF and N, N ′-dicyclohexylcarbodiimide (DCC) which lead to the formation of an intermediate salt of N -cyclohexyl- N -(cyclohexylcarbamoyl)-4-(trifluoromethyl)benzamide with a perfect crystalline structure. The structure of the compound was characterized by FTIR, 1 H NMR and 13 C NMR analysis. The crystal structure is confirmed by single crystal X-ray diffraction analysis. The Structure-Activity Relationship (SAR) studies revealed that substituent of fluoro or trifluoromethyl moiety into the compound had a great effect on the biological activity in comparison to clinically used drugs. Employing computational approaches the compound was further tested for its affinity against potassium protein structure by molecular docking in addition, bioactivity and ADMET properties were predicted through computer aided programs.